Study of CD27 and CCR4 Markers on Specific CD4+ T-Cells as Immune Tools for Active and Latent Tuberculosis Management - Latorre, Irene; Fernández-Sanmartín, Marco A.; Muriel-Moreno, Beatriz; Villar-Hernández, Raquel; Vila, Sergi; Souza-Galvão, Maria L. De; Stojanovic, Zoran; Jiménez-Fuentes, María Á.; Centeno, Carmen; Ruiz-Manzano, Juan; Millet, Joan-Pau; Molina-Pinargote, Israel; et al. (Frontiers in Immunology, 2019)
The immunological characterization of different cell markers has opened the possibility of considering them as immune tools for tuberculosis (TB) management, as they could correlate with TB latency/disease status and outcome. CD4+ T-cells producing IFN-γ+ with a low expression of CD27 have been described as an active TB marker. In addition, there are unknown homing receptors related to TB, such as CCR4, which might be useful for understanding TB pathogenesis. The aim of our study is focused on the assessment of several T-cell subsets to understand immune-mechanisms in TB. This phenotypic immune characterization is based on the study of the specific immune responses of T-cells expressing CD27 and/or CCR4 homing markers. Subjects enrolled in the study were: (i) 22 adult patients with active TB, and (ii) 26 individuals with latent TB infection (LTBI). Blood samples were drawn from each patient. The expression of CD27 and/or CCR4 markers were analyzed within CD4+ T-cells producing: (i) IFN-γ+, (ii) TNF-α+, (iii) TNF-α+IFN-γ+, and (iv) IFN-γ+ and/or TNF-α+. The percentage of CD27− within all CD4+ T-cell populations analyzed was significantly higher on active TB compared to LTBI after PPD or ESAT-6/CFP-10 stimulation. As previously reported, a ratio based on the CD27 median fluorescence intensity (MFI) was also explored (MFI of CD27 in CD4+ T-cells over MFI of CD27 in IFN-γ+CD4+ T-cells), being significantly increased during disease (p < 0.0001 after PPD or ESAT-6/CFP-10 stimulation). This ratio was also assessed on the other CD4+ T-cells functional profiles after specific stimulation, being significantly associated with active TB. Highest diagnostic accuracies for active TB (AUC ≥ 0.91) were achieved for: (i) CD27 within IFN-γ+TNF-α+CD4+ T-cells in response to ESAT-6/CFP-10, (ii) CD27 and CCR4 markers together within IFN-γ+CD4+ T-cells in response to PPD, and (iii) CD27 MFI ratio performed on IFN-γ+TNF-α+CD4+ T-cells after ESAT-6/CFP-10 stimulation. The lowest diagnostic accuracy was observed when CCR4 marker was evaluated alone (AUC ≤ 0.77). CD27 and CCR4 expression detection could serve as a good method for immunodiagnosis. Moreover, the immunological characterization of markers/subset populations could be a promising tool for understanding the biological basis of the disease.